FLASH CARDS’ CONTRIBUTION IN INTRODUCING ENGLISH VOCABULARY TO THE FIRST GRADERS OF SDN BRUMBUNGAN SEMARANG AND THEIR RESPONSES: A CLASSROOM ACTION RESEARCH - Vinna Octavia; Liliek Soepriatmadji (Universitas Stikubank (UNISBANK) Semarang, 2020)
Teaching media becomes one of the problems faced by teachers in teaching English as a foreign language for young learners. The use of appropriate teaching media is essential for teachers to be successful. This study aims to discuss the contribution of flash cards in introducing English vocabularies to the first graders of SDN Brumbungan Semarang. The model of Classroom Action Research by as proposed Kemmis and McTaggart was applied in two cycles and the data were analyzed qualitatively by involving data reduction, data categorization, data synthesis, and stating action hypothesis. The findings show that flash cards can motivate students, help students in remembering vocabulary, and helping teachers in introducing English specific vocabularies more easily. It can be shown that students who were participating in the activities were active, responsive, confident, enthusiastic, and enjoying the learning process. It can be concluded that teaching media used for young learners is really helpful in introducing English. However, teachers should understand the students’ level and have innovations in creating variations in learning activities using teaching media. Keywords: classroom action research, flash cards, English vocabulary, young learners